KELUARGA SEBAGAI BASIS PENDIDIKAN ISLAM DAN PEMBENTUKAN KARAKTER ANAK - Muhammad Kumaidi; Ridho, Elshafa Nur Ahmad; Eka Pitria; Faizal Yusup; Edri Firmansyah; Evi Febriani (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
In Islamic perspective, the family holds a fundamental position as the first educational institution that instills moral, spiritual, and social values in children. Parents bear full responsibility for shaping an Islamic personality through exemplary behavior, affection, and the cultivation of worship habits. This study aims to examine the role of parents in home-based Islamic education and to formulate strategies for nurturing children’s character based on the Qur’an and the Sunnah. The research employs a descriptive qualitative approach using a literature study method that draws from relevant academic sources. The findings indicate that the success of family education is determined by the level of awareness, consistency, and active involvement of parents in the guidance process. Effective strategies for character development include the habituation of worship, spiritual communication, moral exemplification, and compassionate discipline. A household that lives by Islamic values holistically serves as the primary foundation for raising a generation that is faithful, ethical, and strong in character within its social life.